Analisis Determinan Faktor Kepuasan Muzakki Di Yayasan Rumah Bintang Indonesia - Listiasari, Rani; Ali Fikri, Yudistia Teguh; Irawati, Irawati; Muhajir, Ahmad; Maulana, Hendra; Mabruri, Kemal Al Kautsar (Jurnal Ilmiah Ekonomi Islam, 2023)
In total, there are 200 muzakki who have distributed their zakat in the Foundation. As a non-profit organization, Rumah Bintang Foundation has very high demands to be able to collect as much zakat as possible and to utilize the collected zakat effectively and efficiently. This study aims to determine the factors that influence the satisfaction of muzakki in distributing their zakat. This research uses multiple linear regression method with SPSS 20 software. This research uses a quantitative approach. This research is used to examine certain populations or samples. Data collection techniques use research instruments, data analysis is quantitative/statistical in nature with the aim of testing the established hypotheses. Sources of data were obtained through the first data from the Rumah Bintang foundation and through interviews. From the results of the SPSS 20.0 output display, it shows that the adjusted R2 is 0.445, this means that muzakki's satisfaction can be explained by the place, product, promotion, and price variables only by 4.45% while the rest (100% -4.45% = 55.5 %) is explained by other variables. The calculation results produce a calculated F of 14.039 with a significance value of 0.001, because the significant value is less than 0.05 then Ha is accepted and Ho is rejected. So it can be concluded that product, place, promotion, and place have an effect on muzakki's satisfaction. Thus, it can be concluded that the null hypothesis which states "there is no influence between satisfaction factors and muzakki satisfaction" cannot be accepted which means accepting the alternative hypothesis which reads "there is influence between the satisfaction factors variables on muzakki satisfaction."